2009
DOI: 10.3109/s10165-009-0153-5
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of ankylosing spondylitis in an Iranian population of 98 patients

Abstract: The prevalence and pattern of ankylosing spondylitis (AS) can vary from country to country, according to genetic and environmental factors. This study aims to analyze the patterns of disease in a population of Iranian patients with AS. We performed a prospective study (2002-2007) analyzing 98 patients with diagnosis of AS according to the modified New York criteria. Selected patients underwent complete clinical (initial symptom, axial and peripheral involvement, heel enthesitis, extra-articular manifestations)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
4
5
1
Order By: Relevance
“…This study found a higher prevalence of male axSpA patients with HLA-B27, which is in accordance with that previously published in another Chinese research on radiographic SpA, and also similar in a DESIR cohort conducted in patients representing early forms of the whole spectrum of axial SpA (20,21). However, several other studies did not note any differences (16,(22)(23)(24), which may be explained by considering geographic and genetic factors.…”
Section: Discussionsupporting
confidence: 92%
“…This study found a higher prevalence of male axSpA patients with HLA-B27, which is in accordance with that previously published in another Chinese research on radiographic SpA, and also similar in a DESIR cohort conducted in patients representing early forms of the whole spectrum of axial SpA (20,21). However, several other studies did not note any differences (16,(22)(23)(24), which may be explained by considering geographic and genetic factors.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that HLA‐B27 + patients had a higher chance of having a family medical history of AS than HLA‐B27 − peers, which is in line with previous studies (Table ).…”
Section: Demographic Data and Clinical History Of Chinese Ankylosing supporting
confidence: 93%
“…Furthermore, in our study, hip joint involvement was observed more frequently in HLA‐B27 + groups compared with their HLA‐B27 − peers, which is similar to the findings from some recent studies (Table ). Brophy et al suggested that hip involvement was more prevalent among patients with young onset age .…”
Section: Demographic Data and Clinical History Of Chinese Ankylosing supporting
confidence: 92%
See 1 more Smart Citation
“…Meanwhile, population heterogeneity and potential differences in clinical pattern might also serve as possible explanations. The prevalence of enthesitis, including heel pain, was 3.4% in our present study, slightly higher than heel enthesitis in Iranian AS patients (1.9%), 36 but lower than that in Brazilian patients (6.1%) 30 . Kim et al.…”
Section: Discussioncontrasting
confidence: 70%